1999
DOI: 10.1366/0003702991946695
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Excitation Emission Matrices of Human Tissue: A System for in vivo Measurement and Method of Data Analysis

Abstract: We describ e a system capable of measuring spatially resolved reectance spectra from 380 to 950 nm and¯uorescence excitation emission m atrices from 330 to 500 nm excitation and 380 to 700 nm emission in vivo. System performance was compared to that of a standard scanning spectro¯uorimeter. This``FastEEM``system was used to interrogate human normal and neoplastic oral cavity mucosa in vivo. Measurem ents were m ade through a ® ber-optic probe and req uire 4 min total m easurement tim e. We present a method bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(74 citation statements)
references
References 37 publications
(24 reference statements)
1
71
0
2
Order By: Relevance
“…Many types of probes have been used within the research community and cannot all be summarized here; however, comprehensive reviews of DRS, LIFS, and RS probe technology are available. 34 Briefly, combination LIFS-DRS probes have been demonstrated by past studies, 35,36 as well as a probe combining all three techniques. 32 There are several important, and challenging, design and functional considerations for a probe that combines reflectance, fluorescence, and Raman signals.…”
Section: Fiber-optic Probesmentioning
confidence: 99%
“…Many types of probes have been used within the research community and cannot all be summarized here; however, comprehensive reviews of DRS, LIFS, and RS probe technology are available. 34 Briefly, combination LIFS-DRS probes have been demonstrated by past studies, 35,36 as well as a probe combining all three techniques. 32 There are several important, and challenging, design and functional considerations for a probe that combines reflectance, fluorescence, and Raman signals.…”
Section: Fiber-optic Probesmentioning
confidence: 99%
“…The bundle is described in more detail in Ref. [11]. Fluorescence emission collected by the optical ®ber was further isolated by passing the remitted light through a 565-nm longpass (cutoff) ®lter.…”
Section: Intensity Measurementsmentioning
confidence: 99%
“…Several studies have demonstrated that fluorescence spectroscopy can be used for discrimination of normal and malignant oral tissues. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] We have developed a Raman spectroscopy method with specificity and sensitivity better than 95%, for discrimination of normal and malignant tissues in oral cancers. 20,21 Recent Raman microspectroscopy studies of formalin-fixed oral tissues have validated the use of these samples in optical pathology.…”
Section: Introductionmentioning
confidence: 99%